2
$\begingroup$

Belyaev and Sjöstedt-de Luna introduced the notion of weakly approaching sequences of distributions, generalizing the weak convergence without imposing the limiting distribution.

Definition. Two sequences of random variables $\{Y_n\}$ and $\{X_n\}$ are said to have weakly approaching distributon laws, $\{\mathcal{L}(Y_n)\}$ and $\{\mathcal{L}(X_n)\}$, if for any bounded continuous function $f$, $E(f(Y_n))-E(f(X_n))\to 0$ as $n\to\infty$, and we write $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X_n), \ n\to\infty$.

I know that $Y_n$ converges in distribution/weakly to $X$, denoted by $Y_n\overset{d}{\to}X$, if for any bounded continuous function $f$, $E(f(Y_n))-E(f(X))\to 0$ as $n\to\infty$, by portmanteau Lemma.

My question is: when $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X_n)$ will imply $Y_n\overset{d}{\to}X$?

I believe that $X_n\overset{d}{\to}X$ is sufficient. But I cannot argue why.

My attempt

Suppose that $X_n\to X$ in distribution. Then the portmanteau Lemma (see Lemma 2.2 of Van der Vaart's Asymptotic Statistics) gives $\mathcal{L}(X_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X)$. Therefore $$E(f(Y_n))-E(f(X))=E(f(Y_n))-E(f(X_n))+E(f(X_n))-E(f(X))\to 0$$ for any bounded continuous $f$, by hypothesis.

This shows that if $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X_n)$ and $X_n\overset{d}{\to}X$, then $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X)$ . By portmanteau Lemma again, $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X)$ implies $Y_n\overset{d}{\to}X$.

Thanks in advance!

$\endgroup$
  • 2
    $\begingroup$ Just an comment on nomenclature: it's the 'portmanteau lemma', from the word 'portmanteau', indicating that it has a lot of things stuffed in together. It's not named after a Monsieur Portmanteau $\endgroup$ – Thomas Lumley May 21 at 6:40
  • 1
    $\begingroup$ @ThomasLumley thanks $\endgroup$ – Celine Harumi May 21 at 16:58
1
$\begingroup$

This one is a simple case of combining two limits into one. In the present case the condition is necessary and sufficient, so you have a stronger result than the one you are positing.

Theorem: Suppose that $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X_n)$. Then for any random variable $L$ we have: $$X_n\overset{d}{\to}L \quad \iff \quad Y_n\overset{d}{\to}L.$$

Proof: Let $f$ be an arbitrary bounded continuous function, so we have the limit: $$\lim_{n \to \infty} \mathbb{E}(f(Y_n)) - \mathbb{E}(f(X_n)) = 0.$$ ($\implies$) Since $X_n\overset{d}{\to}L$ we have $\lim_{n \to \infty} \mathbb{E}(f(X_n)) - \mathbb{E}(f(L)) = 0$ which gives: $$\begin{aligned} \text{Limit} &\equiv \lim_{n \to \infty} \mathbb{E}(f(Y_n)) - \mathbb{E}(f(L)) \\[6pt] &= \lim_{n \to \infty} \Big[ \mathbb{E}(f(Y_n)) - \mathbb{E}(f(X_n)) + \mathbb{E}(f(X_n)) - \mathbb{E}(f(L)) \Big] \\[6pt] &= \lim_{n \to \infty} \Big[ \mathbb{E}(f(Y_n)) - \mathbb{E}(f(X_n)) \Big] + \lim_{n \to \infty} \Big[ \mathbb{E}(f(X_n)) - \mathbb{E}(f(L)) \Big] \\[6pt] &= 0+0 = 0. \\[6pt] \end{aligned}$$ The proof of the reverse implication ($\impliedby$) is identical. $\blacksquare$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Indeed, if $E(f(Y_n))-E(f(X_n))\to 0$ and $E(f(X_n))-E(f(X))\to 0$, elementary facts about sequences would tell you $$ E(f(Y_n))-E(f(X))\to 0, $$ i.e. (since $f$ is arbitrary bounded and continuous function) $$ Y_n\overset{d}{\to}X. $$

(Necessity also holds as well as sufficiency. Suppose $\mathcal{L}(Y_n) \overset{w.a.}{\longleftrightarrow}\mathcal{L}(X_n)$, then $Y_n$ converges in distribution if and only $X_n$ does also.)

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.